LEVERAGING TIKTOK AS A PROMOTIONAL TOOL: A CASE STUDY OF @tamansafari.prigen - Regista Arandha, Maria (Penerbit Lafadz Jaya, 2024)
The rapid advancement of technology has ushered us into the Fourth Industrial Revolution, emphasizing digitalization, automation, artificial intelligence (AI), the Internet of Things (IoT), and advanced data analytics. This technological evolution has fostered the rise of social media, platforms for interaction, sharing, and content creation. TikTok, a leading platform, has become a potent tool for businesses to promote products and services by posting high-quality content. This study explores how TikTok serves as a promotional avenue for the Taman Safari Prigen tourist attraction. Employing observation and interviews, the research reveals TikTok's capability to enhance brand awareness and attract visitors to Taman Safari Prigen, as highlighted by the AISAS analysis. The study emphasizes the stages of Search, Action, and Share as pivotal promotional opportunities.